Reciprocal Crosstalk Between YAP1/Hippo Pathway and the p53 Family Proteins: Mechanisms and Outcomes in Cancer - Raj, Nitin; Bam, Rakesh (Frontiers in Cell and Developmental Biology, 2019)
The YAP1/Hippo and p53 pathways are critical protectors of genome integrity in response to DNA damage. Together, these pathways secure cellular adaptation and maintain overall tissue integrity through transcriptional re-programming downstream of various environmental and biological cues generated during normal tissue growth, cell proliferation, and apoptosis. Genetic perturbations in YAP1/Hippo and p53 pathways are known to contribute to the cells’ ability to turn rogue and initiate tumorigenesis. The Hippo and p53 pathways cooperate on many levels and are closely coordinated through multiple molecular components of their signaling pathways. Several functional and physical interactions have been reported to occur between YAP1/Hippo pathway components and the three p53 family members, p53, p63, and p73. Primarily, functional status of p53 family proteins dictates the subcellular localization, protein stability and transcriptional activity of the core component of the Hippo pathway, Yes-associated protein 1 (YAP1). In this review, we dissect the critical points of crosstalk between the YAP1/Hippo pathway components, with a focus on YAP1, and the p53 tumor suppressor protein family. For each p53 family member, we discuss the biological implications of their interaction with Hippo pathway components in determining cell fate under the conditions of tissue homeostasis and cancer pathogenesis.